45.2k views
5 votes
Which expression is equivalent to (3m)(4m)2?

Which expression is equivalent to (3m)(4m)2?-example-1
User Cphlewis
by
5.2k points

2 Answers

3 votes
4m^2= (4m)(4m)
=16m^2
=(16m^2)(3m)
=48m^3
User Dizzi
by
5.3k points
3 votes

Answer:


48m^3


Explanation:

We use the rule
(ab)^n=a^n*b^n to first simplify this:


(3m)(4m)^2\\=(3m)((4)^(2)*(m)^(2))\\=(3m)(16m^2)\\=(3*16)*(m)(m^2)


Now we use the rule
a^x*a^y=a^(x+y) we simplify further and find the answer:


(3*16)*(m)(m^2)\\=48m^(1+2)\\=48m^3

The third answer choice is right.

User Ilkin
by
4.9k points